Drugstore Beetle Damage Pattern of Glue Paste-Lined Oil Paintings - Lee, Wen-Yuan; Liu, Kai-Yuan; Wu, Wan-Yu; Tsai, Cheng-Lung; Wu, Wei-An; Li, Hou-Feng (Journal of economic entomology, 2022)
A glue paste lining is a traditional conservation treatment used to reinforce the aged canvas of oil paintings. Several insect infestation cases concerning glue paste-lined oil paintings have been reported around the world, particularly in European countries. In 2008, Chimei Museum, a private museum located in Tainan, Taiwan, was affected by a severe beetle infestation of oil paintings. To confirm the infesting insects and to quantify the damage pattern for further development of control and monitoring methods, three severely damaged paintings were examined along with the restoration procedure. A total of four insect species were collected. The drugstore beetle, Stegobium paniceum (L.) (Coleopter: Ptinidae), was the primary pest found in all three paintings investigated and was identified based on morphological and genetic data. Thrips and booklice were considered secondary pests, and a Pteromalid wasp was speculated to have a parasitic relationship with the drugstore beetle. Drugstore beetle larvae mainly bored into the glue paste layer and original canvas and required only 5.94 ± 1.38 mm3 of feed to grow from egg to pupa. Their bores were not evenly distributed, and most of them were found in the shaded area covered by the stretcher and outer frame. The body length of drugstore beetles varied, ranging from 1.67 to 2.75 mm, which may explain the various sizes of exit holes on gummed tape surrounding the frame. Detailed and quantified information on drugstore beetle's pattern of damage provided in this study will be beneficial for further developing conservation practices and inspection methods.